Using clathrate hydrates for gas storage and gas-mixture separations: experimental and computational studies at multiple length scales. (18th August 2018) - Tsimpanogiannis, Ioannis N.; Costandy, Joseph; Kastanidis, Panagiotis; El Meragawi, Sally; Michalis, Vasileios K.; Papadimitriou, Nikolaos I.; Karozis, Stylianos N.; Diamantonis, Nikolaos I.; Moultos, Othonas A.; Romanos, George E.; Stubos, Athanassios K.; Economou, Ioannis G.
ABSTRACT: Clathrate hydrates have characteristic properties that render them attractive for a number of industrial applications. Of particular interest are the following two cases: (i) the incorporation of large amounts of gas molecules into the solid structure has resulted in considering hydrates as possible material for the storage/transportation of energy or environmental gases, and (ii) the selective incorporation of guest molecules into the solid structure has resulted in considering hydrates for gas-mixture separations. For the proper design of such industrial applications, it is essential to know accurately a number of thermodynamic, structural and transport properties. Such properties can either be measured experimentally or calculated at different scales that span the molecular scale-up to the continuum scale. By using clathrate hydrates as a particular case study, we demonstrate that performing studies at multiple length scales can be utilised in order to obtain properties that are essential to process design. GRAPHICAL ABSTRACT: